Does Feedback Matter? : Evidence from Agricultural Services - Jones, Maria; Kondylis, Florence (Elsevier, 2018)
We design a field experiment to test whether eliciting feedback can affect demand for a service. We randomly assign different feedback tools in the context of an agricultural service and track their impact on farmers' demand. We find large demand effects, in the current and following agricultural seasons. These demand effects spill over, as non-client farmers in the vicinity of treated groups are more likely to sign up. Announcing monitoring to trainers across treatment and control communities has little effect on trainers' effort. We conclude that increasing farmers' control over the quality and content leads their higher demand for the service.